Effects of Stellate Ganglion Block Through Different Approaches Under Guidance of Ultrasound - Shan, Hai-Hua; Chen, Hong-Fang; Ni, Yong; Yang, Jia-Xuan; Zhou, Xue-Lan (Frontiers in Surgery, 2022)
Objective: This study aimed to investigate the effects of stellate ganglion block (SGB) through different approaches under guidance of ultrasound. Methods: A total of 130 patients undergoing SGB in our hospital between February 2019 and February 2020 were enrolled as the research subjects. According to the random number table method, these subjects were divided into two groups: a modified 6th cervical vertebra (C6) group (n = 65) and a 7th cervical vertebra (C7) group (n = 65). Under the guidance of ultrasound, the subjects in the modified C6 group were punctured at the level of the C6 transverse process, and the subjects in the C7 group were punctured at the level of the C7 transverse process. The operation duration, number of puncture angle adjustments, block effects, and adverse reactions for SGB were compared between the two groups. Results: The modified C6 group showed shorter SGB operation duration and a lower number of puncture angle adjustments than the C7 group, and the differences were statistically significant (P < 0.05). Horner syndrome occurred in both groups after SGB. The incidence of adverse reactions in the modified C6 group was 4.62%, comprising 1 case of hoarseness and 2 cases of slowed pulse, while that in the C7 group was 6.15%, with 1 case of hoarseness and 3 cases of slowed pulse; the difference between the two groups was not statistically significant (P > 0.05). Conclusion: The operation duration for modified SGB guided by ultrasound puncturing at the C6 transverse process is shorter and requires fewer puncture angle adjustments than puncturing at the C7 transverse process; however, there is no significant difference between the incidence of adverse reactions or the blocking effects of the two methods.